Knitting in the History of Fashion - Degeniene, Virginija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
Knitting technique is rarely mentioned in overview of costume history. Fashion theorists' attention to knitting is also insignificant because this technique never had significant influence on fashion changes. The intention of article is to overview the evolution of knitting, to inquire about its historic roots and its place in fashion history, to present knitting as creative process and contemporary technology that takes even greater part in world of fashion. I wanted to deny established stereotype that knitting is only handiworks or women's pastime. Gathered, analyzed and systemized information unveils interesting panorama of knitting as creating process having old traditions. Originated in old past, created with extremely simple tools now knit product became a branch of textile and fashion industry. Life of contemporary man is hardly imaginable without knit products. New knitting technologies enter into fashion industry and promote variety and progress of the product.